2016
DOI: 10.1007/s10646-016-1622-1
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and genotoxic assessment of surface water from São Paulo State, Brazil, during the rainy and dry seasons

Abstract: The aim of this study was to determine if the cytotoxic and genotoxic responses of Allium cepa are effective biomarkers of harmful effects caused by polluted river water and if changes in the responses reflect seasonality in the harmful effects. Samples were collected in the dry season (August 2011 and 2012) and rainy season (February 2012 and 2013) at sampling points on the Jaguari River and the Ribeirão Lavapés, in Brazil. Allium cepa bulbs were exposed to the samples, to positive controls (15 µg/L methyl me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 49 publications
1
3
0
2
Order By: Relevance
“…The period of collection of water samples may also have in uenced the cytotoxic and genotoxic effects veri ed, because during rainy periods there is an increase in the ow of water that transports the compounds derived from leaching and percolation from diffuse sources, which can have negative impacts on the environment. Similar results to those observed in our study were also veri ed by Salles et al (2016), who evaluated the dry and rainy seasons and obtained lower MI values and higher CAI values for A. cepa cells exposed to surface water samples from the rainy season in relation to the dry season. Considering the MI and CAI, the cells of A. cepa tested with the water sample of Vitória stream were the ones that most demonstrated inhibition of cell division and induction of chromosomal alterations in relation to the other treatments.…”
Section: Discussionsupporting
confidence: 92%
“…The period of collection of water samples may also have in uenced the cytotoxic and genotoxic effects veri ed, because during rainy periods there is an increase in the ow of water that transports the compounds derived from leaching and percolation from diffuse sources, which can have negative impacts on the environment. Similar results to those observed in our study were also veri ed by Salles et al (2016), who evaluated the dry and rainy seasons and obtained lower MI values and higher CAI values for A. cepa cells exposed to surface water samples from the rainy season in relation to the dry season. Considering the MI and CAI, the cells of A. cepa tested with the water sample of Vitória stream were the ones that most demonstrated inhibition of cell division and induction of chromosomal alterations in relation to the other treatments.…”
Section: Discussionsupporting
confidence: 92%
“…The A. cepa assay revealed that the water and sediments samples collected in the Piauí coast contaminated with sodium metabisulfite induced toxicity and authors revealed that assay may be used as a regular tool in the analysis of water in shrimp farms in the coast of Piauí state for preserving the region's marine ecosystem. More recently, Salles et al (2016) collected water samples from Jaguari River and Ribeirão Lavapés, Brazil in dry season (August 2011 and 2012) and rainy season (February 2012 and 2013) and evaluated for toxic effects. MN, MI and mitotic anomalies were measured in exposed roots.…”
Section: Contaminated River Water/surface Water/sea Watermentioning
confidence: 99%
“…From last few decades, there is a growing concern of pollution, which not only affect the animal and plant, but also human beings as well. The water bodies serve as temporary or final receptors of diverse variety of contaminants, which consequently contaminate the entire watershed and adjoining territories (Barbério et al, 2009;Bianchi et al, 2011;Ghodake et al, 2011;Kumari et al, 2011;Salles et al, 2016). The rapid stride in industrialization is major concern and at present is a severe threat to the survival of living organisms and jeopardizing the ecological balance Iqbal et al, 2013a;Iqbal, 2016;Iqbal et al, 2016b;Islam et al, 2015;Manzoor et al, 2013;Mushtaq et al, 2016;Nadeem et al, 2016a;Rashid et al, 2016;Tabrez and Ahmad, 2011;Ullah et al, 2013;Younas et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The rapid increase in industrialization is alarming regarding the survival of living creatures and is damaging the ecological balance (Iqbal et al 2019). Continued release of untreated industrial wastes/leachates to the rivers contaminates the entire ecosystem (Bianchi et al 2011;Salles et al 2016). The continuous exposure of organisms to dangerous chemical substances may cause chromosomal abnormalities that can cause diseases and affect the human offspring (Leme & Marin-Morales 2009;Mazzeo et al 2018).…”
Section: Introductionmentioning
confidence: 99%